PENGARUH PROPORSI DEWAN KOMISARIS INDEPENDEN, KOMITE AUDIT, FINANCIAL DISTRESS DAN UKURAN PERUSAHAAN TERHADAP AUDITOR SWITCHING (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di BEI Periode Tahun 2014-2019) - Nelyumna; Yetty Murni; Baskara Putratama Arta (FEB-UP Press, 2021)
This study aims to analyze the effect of independent commissioners, audit committee, financial distress and company size on auditor switching. The population of this study were all coal mining companies listed on the Indonesia Stock Exchange for the period 2014-2019 with a total sample of 13 companies selected by purposive sampling method. The data analysis technique uses descriptive analysis and logistic regression using SPSS version 20. The results of hypothesis testing prove that the independent board of commissioners has no effect on auditor switching. The audit committee has a significant effect on auditor switching. Financial distress has no effect on auditor switching. Firm size has no effect on auditor switching.